In Search of Civic Policing: Recasting the 'Peelian' Principles - Loader, I (Springer Netherlands, 2014)
For over a century the so-called 'Peelian' principles have been central to the self-understanding of Anglo-American policing. But these principles are the product of modern state-building and speak only partially to the challenges of urban policing today. In fact, they stand in the way of clear thinking and better practice. In this paper, I argue that these principles ought to be radically recast and put to work in new ways. The argument proceeds as follows. First, I recover and outline the current 'Peelian' principles and argue that they lack the specificity, sufficiency and status required in order to do real work in the governance of policing. Second, I make the case for principles both as a regulative ideal guiding our aspirations for what policing can become and as a means of regulating police work in the here-and-now. I then develop a revised set of principles and indicate, in conclusion, how they can guide the formation of trust-producing and democracy-enhancing practices of civic policing. © 2014 Springer Science+Business Media Dordrecht.